Prolegomena to the History of Israel - Wellhausen, Julius, 1844-1918 (Salt Lake City, UT : Project Gutenberg, 2003)
"Prolegomena to the History of Israel" by Julius Wellhausen is a biblical study published in 1878. This groundbreaking work formulated the documentary hypothesis, proposing that the Torah emerged from distinct sources written at different historical periods. Wellhausen argues that ancient Israelite religion evolved dramatically over time, with the Priestly laws traditionally attributed to Moses actually written during the Babylonian exile. His controversial analysis challenged fundamental assumptions about biblical origins, earning comparisons to Darwin's revolutionary impact on evolutionary science. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Prolegomena_zur_Geschichte_Israels
Release date is 2003-12-01
This etext was produced by Geoffrey Cowling.
Keywords: Jews -- History -- To 70 A.D.; Judaism -- History -- To 70 A.D.; Bible. Old Testament -- Criticism, interpretation, etc